The Role of the Internet in the Process of Radicalization in the Western Balkans - Simonović, Branislav; Popovic, Predrag (NBP. Nauka, bezbednosti, policija, 2023)
In the past few decades Muslim extremists from the Western Balkans states have had a significant involvement in terrorist attacks in Europe. A number of extremists from Bosnia and Serbia recruited citizens from territories of former Yugoslavia and Europe to participate in the Syrian war. The increased radicalization in that part of Europe is a product of wars and the strong influence from Muslim countries on the local Muslim population. The research subject in this paper is the video material posted on YouTube in Bosnian and Serbian with the intention to radicalize the Muslim population from the Western Balkans. The analyzed video materials with radical messages were classified into two groups. Ones that aim at changing attitudes (cognitive radicalization) and the ones that propagate change in behaviour (engaging in violence, murder, terrorist acts, etc.)
Keywords: Radicalization, Muslim Extremism, the Internet, The Western Balkans